Democracy, participation and social transformation (Polis (Santiago), 2018)
Taking into account the limitations that confronts democracy in the context of the ongoing globalization, the author analyses the possibilities of a new relation between people, associations and state institutions. The challenges that face mankind at world scale can not be confronted with the social and political models of the Nation-State territory framework. Democracy still remains the best alternative to these epochal crisis, but a democracy that emerges from a profound transformation of the relationship between those governing and those being governerned, which responds to the new ways of participation that the different social actors demand, without the need of going back to a rigid state centralism.
Keywords: democracy; globalization; participation; market; crisis; change